Personnel for creative industries in the cultural space of the Sverdlovsk region - Natalia O. Verbitskaya; Svetlana N. Uchaykina; Larisa V. Vakar (Управление культурой)
The basis of the cultural development of the Sverdlovsk region is the developing cultural activity, primarily on the basis of state and municipal regulation through budget financing. It is combined with creative practices free from state regulation in a common cultural space, common and indivisible for the inhabitants of the region - consumers of the cultural product. The basis of the cultural development of the Sverdlovsk region is a creative complex that develops both in space and in time, which made it possible to form a significant personnel potential of cultural industries. The article discusses six main sources of development and self-development of personnel in the creative industries in the Sverdlovsk region: education of creative individuals in a multi-level system of cultural institutions; intergenerational transfer of experience in creative projects and initiatives; cultural intelligentsia of large, small, medium-sized cities and rural settlements; spaces of creative economy; points of growth for creative initiatives and projects; digitalization of cultural practices and industries. The article also presents development trends and contradictions in the economic thinking of personnel for creative industries in the Sverdlovsk region.